2010
DOI: 10.2460/javma.237.8.936
|View full text |Cite
|
Sign up to set email alerts
|

Biological behavior of oral and perioral mast cell tumors in dogs: 44 cases (1996-2006)

Abstract: Results suggested that in dogs with MCTs arising from the oral mucosa, oral mucocutaneous junction, or perioral region of the muzzle, the presence of regional lymph node metastasis at the time of diagnosis was a negative prognostic factor. However, prolonged survival times could be achieved with treatment. In addition, CCR7 expression in the primary tumor was not significantly associated with the presence of regional lymph node metastasis or survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 54 publications
6
77
0
2
Order By: Relevance
“…Another study has also shown that the prevalence of nodal metastases is higher in dogs with higher grade cutaneous tumours compared with low or intermediate‐grade tumours . The results of this study are consistent with a recent article which described 72% of dogs with oral and peri‐oral MCTs as having nodal metastases at presentation . MCTs arising from the canine muzzle have also been suggested to have a higher metastatic rate at the regional nodes .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Another study has also shown that the prevalence of nodal metastases is higher in dogs with higher grade cutaneous tumours compared with low or intermediate‐grade tumours . The results of this study are consistent with a recent article which described 72% of dogs with oral and peri‐oral MCTs as having nodal metastases at presentation . MCTs arising from the canine muzzle have also been suggested to have a higher metastatic rate at the regional nodes .…”
Section: Discussionsupporting
confidence: 91%
“…This is a descriptive study outlining the presentation, signalment, metastatic behaviour, treatment and outcome of 33 dogs with MCTs arising from the oral mucosa. Previously only a much smaller number of cases have been specifically described affecting this site, and these tumours appear to have a different biological behaviour than their more common cutaneous counterparts …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several anatomical sites have been associated with more aggressive tumours and a more guarded prognosis; these sites include mucocutaneous junctions, oral mucosal, muzzle, subungual locations, and perineal and scrotal MCT (London and Thamm 2013, Elliot and others 2013, Hillman and others 2010). Conjunctival MCTs appear to carry a more favourable prognosis (Fife and others 2011).…”
Section: Presentationmentioning
confidence: 99%